1996
DOI: 10.1007/bf02091520
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancer a comparative study among clinicopathologic features, AgNORs, and DNA content analysis

Abstract: A comparative study among clinicopathologic features, silver-stained nucleolar organizer region associated proteins (AgNORs), and DNA content analysis in 76 patients with gallbladder cancer was performed. The AgNOR count, AgNOR area, and the ration of AgNOR area to nuclear area were significantly higher in patients with a low grade of histological differentiation and deep invasion into the gallbladder wall. Moreover, these parameters were higher in cases with lymph node involvement and distant metastases. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…In contrast to the study by Nishizawa-Takano et al where there was no significant difference in AgNOR count amongst GBC patients in relation to sex, in our study mean AgNOR count in both GBC and chronic cholecystitis was higher in males as compared to females with statisitcally significant (p=0.024) difference seen in GBC subset in relation to sex. Mean AgNOR counts was higher in Adenocarcinoma compared to other histological subtypes but statistical analysis revealed no significant difference which is consistent with the findings as reported by Nishizawa-Takano et al [22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to the study by Nishizawa-Takano et al where there was no significant difference in AgNOR count amongst GBC patients in relation to sex, in our study mean AgNOR count in both GBC and chronic cholecystitis was higher in males as compared to females with statisitcally significant (p=0.024) difference seen in GBC subset in relation to sex. Mean AgNOR counts was higher in Adenocarcinoma compared to other histological subtypes but statistical analysis revealed no significant difference which is consistent with the findings as reported by Nishizawa-Takano et al [22].…”
Section: Discussionsupporting
confidence: 91%
“…Nishizawa-Takano et al reported that an increased number and increased size of AgNOR dots were significantly associated with lymph node metastasis, distant metastasis and shorter survival of patients who had undergone surgical resection of gallbladder cancers [22]. They concluded that AgNOR number and AgNOR area, together with depth of neoplastic invasion and lymph node metastasis appear to be independent prognostic factors for survival in patients with gallbladder cancer [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the proportion of aneuploid tumours with T stage (Table 1) supports the concept of a change from diploid to aneuploid DNA patterns in course of tumour development. This concept is further supported by our observation of the coexistence of diploid and aneuploid tumour biopsies in the same tumour, also described by Nishizawa et al [24].…”
Section: Discussionsupporting
confidence: 90%
“…While our results showed significant numerical aberrations in gallbladder carcinomas, further studies using a larger sample size should be conducted, and examination of gallbladder tissue for numerical aberrations on other chromosomes is also necessary. Recent studies from our laboratory showed that increased proliferation activity reflecting argyrophilic nucleolar organizer region‐associated proteins (AgNORs) was significantly associated with the carcinogenesis, development, and prognosis of gallbladder cancers 25. Therefore, acrocentric chromosomes related to AgNORs26 are a target for future analysis of gallbladder carcinomas in our laboratory.…”
Section: Methodsmentioning
confidence: 93%